O DIREITO AO MEIO AMBIENTE DO TRABALHO EQUILIBRADO E SEM DISCRIMINAÇÃO: UM DIREITO FUNDAMENTAL NA CONSTITUIÇÃO BRASILEIRA DE 1988 - Graciane Rafisa Saliba (TRF2, 2018)
The environment outlined in the Constitution of the Federative Republic of Brazil made in 1988, in a holistic interpretation, encompasses even the labor sector. Compliance with health, safety and hygiene standards are essential in the work environment, and also the organizational climate and non-discrimination, promoting human dignity and valorization of the worker are considered human rights, raised to constitutional treatment. It seeks to prevent incidents and misfortunes, as well as the fight against discrimination, subjectively or objectively, when there is a disrespect to the rules, with the aim of discouraging the non-observance by employers or workers. The respect and care for the environment and the people, especially in the field of work, is in keeping with the social function of property, provided by article 170 of the 1988 Brazilian Constitution, as well as fulfills the requirements of articles 225 and 5, XLI of the same instrument, which are therefore a fundamental right. In order to approach the theme, a bibliographical review was used, with exploratory and explanatory research, using a deductive method, based on general and pre-established knowledge that led to the need for non-discrimination in the work environment to achieve human dignity.